The role of neighborhood and cantonal sports leagues in the development of communities community development: an approach to strengthening local development - Sisalema Morejón, Lila Arcelia; Cabrera Mendoza, Cristhian Josue (Conexiones UG, 2024)
The neighborhood and cantonal sports leagues are considered an arm of the economy in the community, however, it has been detected that these sports organizations are unaware of the good administrative, accounting, tax and financial practices by those who make up the leagues, which does not allow for better control of the assigned resources or the fulfillment of their established plans regarding the popularization of sport, both in urban and rural areas, therefore the immediate effect is the non-compliance with the delivery of periodic financial reports and progress of results achieved within the annual planning. The aim is to analyze the socioeconomic level of the neighborhood and cantonal sports leagues that have been part of the community services project between the University of Guayaquil and the Ministry of Sports and to establish how local development and the participation of the academy through the connection with society affects the quality of life of the community. This community strengthening translates into additional benefits, such as greater collaboration in local initiatives and a sense of shared identity. The methodological approach in this study is of a mixed type based on secondary information through surveys and documentary information collected from sports organizations and users of their facilities. According to the results obtained through sports organizations and users of neighborhood and cantonal sports leagues, it was evident that the existence of these leagues plays a crucial role in strengthening local development. The data collected indicate that these leagues contribute significantly to the creation of opportunities for different citizens to participate in sports training activities, in addition to recreational and/or leisure activities.
Keywords: Local development; Sports; Community outreach; Economy; Community